IBM COE authorized testing center examination management system - Teng, Siew Ling (2014)
The general paper-pen exam management system are now slowly being replaced by the online internet based management system. For universities managing the examination have never been easy. Now university can manage examination very easily. The Examination Management System is a web based application. The system can be modified and customized to suit the user requirement. This software is particularly suited to IBM Testing Center as it will save valuable time spent on assessing the register to take exam and the results of exam can be obtained in a short time. This system software offers web based examination management software. It enable students to register online and pick the date of taking exam. Whole system is controlled by administrator. The software maintains the details for each student as well as provides an admin for editing the student details if required. There is password based access for student and admin to access the system. But only the admin are allow to change the data in the system. Authentication is provided via sessions and the password is stored in the database. Admin set exam date and seat layout for student. The task of maintaining the record of result of the tests for which a particular candidate has appeared will be done by the admin.